2001
DOI: 10.1149/1.1339867
|View full text |Cite
|
Sign up to set email alerts
|

A Photorechargeable Metal Hydride/Air Battery

Abstract: Photorechargeable air batteries, which discharge by reducing oxygen in the air and which can be charged by light irradiation, are new types of secondary batteries. We have investigated recharging this type of battery via the photoelectrochemical reaction that occurs at its metal hydride-semiconductor/electrolyte interface. This paper discusses the photorecharging capability of an air battery using a metal hydride anode, namely, a SrTiO 3 -LaNi 3.76 Al 1.24 H n ͉KOH͉O 2 cell. We have confirmed that our new nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Consequently, the different energy conversion and storage parts do not match ideally for an effi cient electron transfer. Polymer electrolyte bilayer fi lm with photo-rechargeable characteristics Layer consists of anionically conducting fi lm n/a [74] Photo-rechargeable metal air battery Anthraquinone containing polymers as active anode material, MnO 2 /carbon composite as cathode material η storage = 62 to 72% [76] Catalytic cathode and a photoanode with SrTiO 3 n/a [77] Furthermore, geometrical restrictions limit the effi ciency of the devices.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the different energy conversion and storage parts do not match ideally for an effi cient electron transfer. Polymer electrolyte bilayer fi lm with photo-rechargeable characteristics Layer consists of anionically conducting fi lm n/a [74] Photo-rechargeable metal air battery Anthraquinone containing polymers as active anode material, MnO 2 /carbon composite as cathode material η storage = 62 to 72% [76] Catalytic cathode and a photoanode with SrTiO 3 n/a [77] Furthermore, geometrical restrictions limit the effi ciency of the devices.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, photo‐responsive behavior could also be introduced into the anode for the air‐based battery, which integrated with a traditional air cathode. There are several attractive studies have been reported to demonstrate the concept to date . In 2001, Akuto et al.…”
Section: Photo‐responsive Batteries With Dual‐solid Active Materialsmentioning
confidence: 99%
“…To construct this type of novel bi-functional FCB system, the electrode materials are required to possess the following characteristics: (i) the negative electrode materials should be reduced by hydrogen gas (gaseous charging) and be oxidized during electrochemical reactions and (ii) the positive electrode materials should be oxidized by oxygen gas (gaseous charging) and be able to be reduced electrochemically [8]. Metal hydrides (MHs) are well suited for the negative electrode of the FCB system because they adsorb gaseous hydrogen [7,[10][11][12][13][14][15][16] and have been used as active materials in NiMH secondary batteries [15][16][17][18][19][20][21] as well as in air-metal batteries [11,[22][23]. It has been reported that MH can be rapidly charged to more than 70% of its theoretical capacity within 10 min by pressurized (0.3 and 0.5 MPa) gaseous hydrogen and that the charged MH can be electrochemically discharged by the reactions shown below [7]:…”
Section: Introductionmentioning
confidence: 99%